Understanding proximity mobile payments adoption in South Africa: A perceived risk perspective - Charlene Eksteen; Michael Humbani (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
Although existing literature claims that consumers are ready for proximity mobile payments, the reality is that adoption is still low in South Africa. Service providers' attempts to translate this potential into profit is hindered by consumers' perception of risks associated with proximity mobile payments. The purpose of this study was to investigate the perceived risk dimensions as possible inhibitors of proximity mobile payment adoption, as well as to investigate the role of gender differences, drawing from the perceived risk and push-pull theories. Using a convenience sample, data was collected from South African smartphone users, from whom 284 valid online surveys were obtained. The standard regression analysis reveals that financial-security and performance risk are predictors of proximity mobile payment adoption, and that product risk is not a significant predictor, at least in the South African context. The findings also reveal that both genders feel more or less the same about the influence of risk factors on the adoption of mobile proximity payments, except for performance risk. The results also show that females are more concerned about the performance of proximity mobile payments than males. The study provides tangible insights that service providers and marketers can use to guide application development and communication with consumers. A contribution is also made to the limited empirical research on the influence of proximity mobile payment risks on adoption during crisis times.
Keywords: M31; L81; 650; financial-security risk; performance risk; product risk; proximity mobile payments; adoption intention; perceived risk theory